2020
DOI: 10.3390/antiox9090858
|View full text |Cite
|
Sign up to set email alerts
|

SIRT1/SIRT3 Modulates Redox Homeostasis during Ischemia/Reperfusion in the Aging Heart

Abstract: Ischemia/reperfusion (I/R) injury is the central cause of global death in cardiovascular diseases, which is characterized by disorders such as angina, stroke, and peripheral vascular disease, finally causing severe debilitating diseases and death. The increased rates of morbidity and mortality caused by I/R are parallel with aging. Aging-associated cardiac physiological structural and functional deterioration were found to contribute to abnormal reactive oxygen species (ROS) production during I/R stress. Distu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 154 publications
(187 reference statements)
3
34
0
Order By: Relevance
“…Previous studies have found that Ang II cause hypertension and hypertensive cardiac hypertrophy and fibrosis 23,24 . SIRT3 can protect the heart from multiple types of diseases which cause cardiac hypertrophy and fibrosis, through the regulation of oxidative stress, metabolism and aging 14,25‐27 . It was consistent with the previous study that SIRT3 deficiency aggravated Ang II‐induced heart injury.…”
Section: Discussionsupporting
confidence: 89%
“…Previous studies have found that Ang II cause hypertension and hypertensive cardiac hypertrophy and fibrosis 23,24 . SIRT3 can protect the heart from multiple types of diseases which cause cardiac hypertrophy and fibrosis, through the regulation of oxidative stress, metabolism and aging 14,25‐27 . It was consistent with the previous study that SIRT3 deficiency aggravated Ang II‐induced heart injury.…”
Section: Discussionsupporting
confidence: 89%
“…Our previous study showed that Moringa oleifera leaf extract (MOLE), due to the presence of glucosinolates, flavonoids and phenolic acids, improved oxidative capacity in C2C12 skeletal muscle cells, as displayed by the increased reliance on fat metabolism through the activation of the SIRT1-PPARα pathway [ 21 ]. Indeed, a number of studies has shown that SIRT1, besides being a critical energy sensor able to modulate transcription factors involved in muscle mitochondrial biogenesis and function [ 22 , 23 ], is also involved in maintaining cellular redox homeostasis [ 24 , 25 ]. In fact, this protein is very effective in attenuating oxidative stress through the deacetylation of transcription factors, including nuclear factor erythroid 2-related factor (Nrf2) [ 26 ], and in such a way potentiates the cellular defense system.…”
Section: Introductionmentioning
confidence: 99%
“…NAD + is also a rate-limiting co-substrate for sirtuin family proteins (SIRT1-7), which all serve as important regulators of redox homeostasis and are implicated in various cardiac diseases [ 189 , 190 ]. NAD + depletion will thus lead to reduction in the activity of SIRT1 [ 191 ] and SIRT3 [ 192 ], which impairs mitochondrial biogenesis and antioxidant defense, further enhancing mitochondrial dysfunction, one of the hallmarks of IRI [ 193 ] ( Figure 4 ).…”
Section: Oxidative Dna Damage and Repair In Ihdmentioning
confidence: 99%